Strategies for xylitol purification and Crystallization: A review - Martínez, Ernesto A.; Canettieri, Eliana V. [UNESP]; Bispo, José A. C.; Giulietti, Marco; De Almeida e Silva, João B.; Converti, Attilio (Taylor & Francis, 2015)
This paper reviews the literature on the main aspects of purification and crystallization of xylitol produced either by chemical or biotechnological routes. Different strategies have been used to clarify media containing xylitol: activated charcoal, pH adjustment, ion-exchange resins, membrane separation, chromatographic methods, liquid-liquid extraction, and precipitation, or a combination of these techniques. This study explores the most recent results of research work carried out in this field as well as the main approaches to recover and crystallize xylitol in a pure form. The effects of impurities, temperature, supersaturation, crystal seed amount, and size on xylitol crystal growth are also discussed.
Keywords: Biotechnological production; Chemical production; Crystallization; Purification; Xylitol